ELISA y técnica de sedimentación espontánea para el diagnóstico de infección por Giardia lamblia en muestras fecales de niños de Perú. - Rodríguez-Ulloa, C.C. (2012)
Objective: To compare a commercial coproantigen ELISA kit and the technique of spontaneous sedimentation in tube (TSET) for the diagnosis of Giardia lamblia in fecal specimens from children in a Peruvian endemic area. Material and methods: 174 fecal samples were analyzed by TSET and 2nd Generation Giardia ELISA kit. Results: 51 samples were positive by ELISA and 49 by TSET. Conclusions: The ELISA was highly sensitive and specific, simple and fast. However, the very good agreement, high precision, low cost and ability to detect other intestinal parasites makes use of TSET recommended for laboratory diagnosis in endemic areas of Peru.